Risks, Benefits, Opportunities, and Electronic Formalities in the Law of Wills: A Comparative Approach - Hall, Margaret; Cockburn, Tina; Crawford, Bridget; Harding, Rosie; Purser, Kelly (McGill Law Journal / Revue de droit de McGill, 2025)
Traditional “formalities” in the law of wills—including formal requirements for revocation by destruction—contemplate paper documents, wet signatures, and testators and witnesses in the physical presence of one another. Unless these traditional requirements have been modified by legislation, wills made using one or more electronic formalities will not meet the formal requirements for a valid will. Traditional wills formalities have become something of an outlier as the use of electronic text, records, signatures, and witnessing has become routine in many spheres, including for the creation and storage of valid legal agreements. The special nature of wills, and their consequent vulnerability to fraud and reliance on documentary evidence of intent, has been cited as a justification for retaining traditional formalities. This article examines the risks, benefits, and opportunities associated with electronic formalities, as well as their implications for wills storage, the assessment of testamentary capacity, and related issues. It also evaluates the adequacy of dispensing provisions as an alternative to electronic formalities. The article includes contributions by coauthors in four common law jurisdictions—England and Wales, British Columbia, Queensland, and New York—with a discussion of how the risks, benefits, and opportunities presented by electronic formalities and wills have been perceived and balanced within each of these jurisdictions.